Development and application of microsatellite markers in Hippophae rhamnoides subsp. sinensis Rousi (Hippophae rhamnoides L.) based on transcriptome sequencing - Liu, Qingqing; Ye, Guisheng; Ma, Yuhua (Frontiers in Genetics, 2024)
Hippophae rhamnoides subsp. sinensis Rousi is a cold-and drought-tolerant pioneer species with significant economic and ecological value. Evaluating its genetic diversity and population structure is of great importance for guiding the development and utilization of resources. In this study, a total of 41,804 SSRs were generated by transcriptome sequencing of Hippophae rhamnoides subsp. sinensis Rousi. Among the different SSR motif types, mononucleotide repeats (26,972) were the most abundant, followed by trinucleotides, tetranucleotides, and pentanucleotides. 200 pairs of SSR primers were selected to detect polymorphisms, of which 15 pairs primers were selected as validated polymorphic SSRs used for genetic diversity and population structure analysis. A total of 63 alleles were identified with 15 pairs primers, with Nei's genetic diversity index ranged from 0.27 to 0.83 (average: 0.54), and the expected heterozygosity ranged from 0.16 to 0.73 (average: 0.46). The polymorphism information content ranged from 0.23 to 0.81 (average: 0.48). Genetic structure analyses showed that the 10 populations could be broadly categorized into 2 groups. AMOVA denoted that genetic variations primarily originated from within the populations, with minimal differences observed between the groups, accounting for only 7% of the total genetic variation. This implies that mutation in Hippophae rhamnoides subsp. sinensis Rousi mainly occurred within the populations. The results showed that the 10 populations of Hippophae rhamnoides subsp. sinensis Rousi are rich in genetic diversity, with low levels of population differentiation and a high degree of gene exchange, which should be taken into consideration for the future work of germplasm resource preservation and seedling breeding.